(3GdMeGjI GdLfGFjI ddMjGI GdNGUI aj GdbGfhf GddjHj (B: s (3OQGSI ebGQfI (B/ s - (3SYGO Ydj eMeO Gdabjgs; (3YeQ eMeO SGde s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2013)
(3Ef JTYH h GJSGY fWGb GdMjGI GdNGUI ; jLYd ef GdUYH GdEdeGe HGdehVhY ef cd LhGfHg (B: (3h jLYd ef GdUYH HecGf Ydi Cj ef GdHGMKjf Cf jVY fXQjI YGeI ddMjGI GdNGUI (B: (3EdG Efg aj gPG GdHMK MGhd GdHGMK Cf jJfGhd (B- (3h dh HLRA HSjW (B- (3MeGjI Mb GdEfSGf aj Cf JXd MjGJg GdNGUI HYjOB Yf CYjf GdeJWadjf (B: (3Ch GfJgGcgG ef bHd GdSdWI GdYGeI (B: (3h bO cGf Sba GdMeGjI aj GdJTQjYjf GddjHj h GdeUQj dG jJYOj MQeI GdeScf h GdJUfJ Ydj GdecGdeGJ GdgGJajI h GdGWdGY Ydi GdeQGSdGJ (B: (3Ch MeGjI GdUhQI(B: (3h bO COi GdJbOe GdYdej h GdJcfhdhLj Edi XghQ eNGWQ LOjOI Ydi MQeI GdMjGI GdNGUIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2013s
(3HHdjhLQGajG(B: (3UaMGJ (B782-814s
Keywords: (3JaJjT GdGTNGUs; (3GdMbhb hGdMQjGJs; (3GdMjGI GdYGFdjIs; (3GdMb ai GdMjGIs; (3GdcQGeI GdGfSGfjIs; (3GdJWhQ GdJGQjNi ddMb ai GdMjGI GdNGUIs; (3LQGFe GdGYJOGA Ydi GdGTNGU s; (3GdhSGFd GdeGSI HGdMjGI GdNGUIs; (3GdcjGf GdeGOi hGdfaSi ddGfSGfs; (3GdhVY JMJ GdeQGbHI GdEdcJQhfjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs